Improved Performance of Village-Owned Enterprises (BUMDes) - Geru, Silfiani; Isa, Rusli; Sholihin, Dwi Indah Yulianti (Public Policy Journal, 2025)
This study aims to describe the performance of Village-Owned Enterprises (BUMDes) in Paku Selatan Village, Bolangitang Barat Sub-District, Bolaang Mongondow Utara Regency. The analysis is based on four main indicators, namely: (a) Efficiency, (b) Effectiveness, (c) Equity, and (d) Responsiveness. The research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the performance of Village-Owned Enterprises (BUMDes) in Paku Selatan Village, Bolangitang Barat Sub-District, Bolaang Mongondow Utara Regency, using the Kumorotomo indicators, has not been optimal. Out of the four indicators used, the performance of the independent BUMDes in Paku Selatan Village showed a significant decline in efficiency, effectiveness, fairness, and responsiveness. Efficiency decreased due to a lack of innovation and weak management, leading to some business units ceasing operations and failing to generate income. Low effectiveness was evident from the limited number of operational business units and a lack of transparency, which eroded public trust. Dependence on a single individual in financial management also reflects unfairness in task distribution. Meanwhile, weak responsiveness to criticism and community aspirations further exacerbates the condition of BUMDes, and during this period, no village revenue (PADes) was generated from BUMDes. Based on the research results, it is evident that efficiency and effectiveness have declined due to weak management, innovation, and asset utilization. Inequality in management indicates low levels of fairness and equitable participation. Responsiveness to community needs is also weak due to a lack of transparency and coordination. Research recommendations include improving governance based on transparency, accountability, and sustainable strategies. Board members need managerial training, asset maximization, and innovation aligned with community needs. Further research is recommended to expand the scope of variables.